APLIKASI MOBILE E-VOTING STUDI KASUS DI-INSTITUTE FOR RESEARCH and EMPOWERMENT (IRE) YOGYAKARTA BERBASIS ANDROID - Gloriansi Umbu Heingu Deta; Erna Kumalasari N; Amir Hamzah (Jurusan Informatika INSTITUT SAINS & TEKNOLOGI AKPRIND YOGYAKARTA, 2016)
Institute for Research and Empowerment (IRE) Yogyakarta is a survey institution established in 1994. It has purpose to ease the respondent for completing the dynamic data interactively. E-voting mobile application is used to perform the survey study in society focused on government policy or social conditions that examined by IRE.There are three steps in doing the poll process. Firstly, the users register in the application, and then do the poll for some survey. After that, the user can get the result of the survey in form of the data and recapitulation of the data.The process of completing the survey is easy and interactive. The application is supported by dynamic data utilizes My SQL data base system. The system was divided into applications. They are mobile application and administrator web. The administrator web is used to process the data. Almost all of types of android version are able to run this application so the respondents will be easy to install and run the application.